Technology Criteria for the Manufacturing of Rebamipide Film-coated Tablets - G. V. Trusov; B. V. Brovchenko; Z. M. Kozlova; I. I. Krasnyuk (Разработка и регистрация лекарственных средств, 2023)
Introduction. The current growth of the pharmaceutical market and stiff competition require from drug manufacturers make a more detailed and thorough fine-tuning of existing production lines. Direct compression technology is a modern and cost-effective technology for solid dosage form drug manufacturing. Roll-compaction tehnology (dry granulation) can be an alternative approach to optimize the manufacturing of formulations, for which the use of wet granulation or direct compression technologies is not possible due to their physical and chemical properties.Aim. The goal of this work is to investigate the possibility of manufacturing Rebamipide tablets by using direct compression technology and dry granulation technology (roll-compaction), avoiding such complicated and more expensive technology as wet granulation. Also aim of this work is study the impact of production methods on such quality factors as disintegration and dis-solution time.Materials and methods. In this study were used such materials as Rebamipide substance (α-[(4-Chlorobenzoyl)amino]-1,2-dihydro-2-oxo-4-quinolinepropanoic acid) (experimental sample), MCC-102 (J. Rettenmaier & Söhne (JRS), Germany), Starch pregelatinized (Colorcon LTD., England), Kollidone SR (BASF, Germany), Croscarmellose sodium (J. Rettenmaier & Söhne (JRS), Germany), Anhydrous citric acid (Scharlau), Sodium lauryl sulfate (BASF, Germany), Aerosil 200 vv Pharma (Evonik Industries AG, Germany), Sodium stearyl fumarate (J. Rettenmaier & Söhne (JRS), Germany), Calcium stearate (FACI, Italy), Film coating VIVACOAT® PA-1P-000 (J. Rettenmaier & Söhne (JRS), Germany). Also were used such equipment as Y shape blender («AZT FARMA K.B.», Russia), roll compactor LGC100 (Beijing Gylongli Automation Tech. Co., Ltd, China), rotary tablet press PG16G (Beijing Gylongli Automation Tech. Co., Ltd, China), tablet coating system Labcoat™ M (O'Hara Technologies lnc, Canada), ionising air gun Simco Cobra (SimcoIon, Netherlands), flowability tester ERWEKA GT (ERWEKA GmbH, Germany), powder density tester ERWEKA SVM 122 (ERWEKA GmbH, Germany), vibrating sieve CISA RP 200N (CISA Cedaceria Industrial S.L., Spain), tablet hardness, thickness and height tester SOTAX HT 10 (SOTAX AG, Switzerland), dissolution tester DT 626/1000HH (ERWEKA GmbH, Germany) and disintegration tester ZT321 (ERWEKA GmbH, Germany).Results and discussion. In a series of experiments were obtained tablet’s cores and film coated tablets by direct compression and roll-compaction methods. Experimentally it was found, that in tablets with similar formulations roller compaction technology provides slower disintegration and dissolution time, compared to direct compression method. This fact should be taken into account during drug development when planning the rate of release of the active ingredient.Conclusion. As a result of the experiments it was shown a direct correlation between the use of a certain technology and its impact in such quality indicators as disintegration and dissolution time of tablets. It was also found that dry granulation technology provides a more technologically suitable tablet mass.